Ecclesiastical Properties as Common Goods: A Challenge for The Cultural, Social and Economic Development of Local Communities - Dimodugno, Davide (Sens public, 2024)
According to recent studies, there are about 600,000 places of worship and several thousand monasteries and convents in Europe. The process of secularization, the decrease and displacement of the population, and the reduction of vocations to the sacred life can be held responsible for the redundancy of the assets of the Catholic Church. These buildings represent an impressive heritage of faith, work and creativity of the communities who built them over the centuries. Most of them are considered “cultural heritage” by the legislation of the European States, because of their historical, cultural, and artistic values. Until now, the main solution to this phenomenon consisted in the alienation of these properties either to municipalities or private investors, sometimes for new uses of general interest, sometimes as residential buildings, or commercial activities. However, selling and disposing of these goods by ecclesiastical bodies cannot always be the only and preferable solution. Drawing from the analysis of some case studies of disused churches, convents and monasteries in Italy, this paper aims to investigate the role of civil society participation in the regeneration process and the possibility of applying “collaboration pacts” for the management of “common goods”, in spite of their legal status (public or private ownership). In light of the European scope of the phenomenon, this article provides a comparison based on the legal instrument of “strategic plans”, drawn up by the diocesan bishop and local authorities in Flanders (Belgium). This article aims to show that the adaptive reuse of ecclesiastical properties can be approached in an innovative way by using the theory of the commons and related legal solutions. This could be a great opportunity for the cultural, social and economic development of cities and villages, all the more so if the whole civil society is involved in the decision of the new functions and subsequent management.